Vasodilation and Hypotension of CZ454, an Analogue of Lacidipine through Inhibiting Extracellular Calcium Influx - Zhang, L.-X.; Zhang, S.-Q.; Cao, Y.-X. (Arzneimittelforschung, 2012)
The aim of this study was to evaluate the effects of an analogue of lacidipine, CZ454 in in vitro and in vivo. The isometric tension of Sprague-Dawley rat arterial ring segments was recorded by a myography system. Intracellular calcium of vascular smooth muscle was determined by the confocal laser microscopy. Blood pressure of spontaneously hypertensive rats was measured using a tail-cuff blood pressure system. The results showed that CZ454 (10 − 9–10 − 6 mol/L) relaxed the mesenteric artery contracted by high K +  concentration-dependently, which was not affected by removal of the endothelium. CZ454 treatment shifted the concentration-contractile curves induced by phenylephrine, U46619, KCl and CaCl2 to the right with the decreased Emax. CZ454 was more potent in the coronary and basilar artery than in the mesenteric artery. CZ454 did not reduce phenylephrine-induced vasoconstriction; however, it did inhibit the contraction caused by addition of CaCl2 and did not change caffeine-induced contraction in the mesenteric artery in Ca2 + -free solution. CZ454 decreased the vasoconstriction induced by Bay K 8644 in the presence of 60 mmol/L K + . CZ454 1.0 mg/kg administered by gavage lowered the systolic pressure and diastolic pressure by 20% and 17%, respectively. It was concluded that CZ454 lowers blood pressure and relaxes arteries with higher potency in coronary and basilar artery and that the vasodilation may involve inhibition of calcium influx.
Keywords: CZ454; lacidipine; vasodilator; hypertension; calcium